Effect of GA-sensitivity on wheat early vigor and yield components under deep sowing - Amram, Avishay; Fadida-Myers, Aviya; Golan, Guy; Nashef, Kamal; Ben-David, Roi; Peleg, Zvi (Frontiers in Plant Science, 2015)
Establishment of seedlings is a key factor in achievement of uniform field stands and, consequently, stable yields. Under Mediterranean conditions, soil moisture in the upper layer is limited and seedlings may be exposed to frequent dehydration events. The presence of the Rht-B1b and Rht-D1b semidominant dwarfing alleles results in insensitivity to gibberellin (GAI) and, hence, poor emergence from deep sowing. Introduction of alternative dwarfing genes and, thereby, preservation of the gibberellin response (GAR) and coleoptile length, contributes to better emergence from deep sowing. Initially 47 wheat cultivars carrying different Rht alleles were screened for their ability to emerge from deep sowing, and then 17 of them were selected for detailed physiological characterization in the field. The modern wheat lines containing GAI alleles showed significantly lower percentages of emergence from deep sowing than the GAR lines, i.e. 52 and 74%, respectively. Differences in early developmental stages were associated with grain yield, as indicated by a reduction of 37.3% in the modern cultivars. Our results demonstrate the potential of alternative dwarfing genes for improving seedling establishment and grain yields in Mediterranean-like environments.